A bottom-up view of food surplus: using stable carbon and nitrogen isotope analysis to investigate agricultural strategies and diet at Bronze Age Archontiko and Thessaloniki Toumba, northern Greece. Issue 1 (1st January 2017) - Nitsch, Erika; Andreou, Stelios; Creuzieux, Aurélien; Gardeisen, Armelle; Halstead, Paul; Isaakidou, Valasia; Karathanou, Angeliki; Kotsachristou, Dimitra; Nikolaidou, Daphne; Papanthimou, Aikaterini; Petridou, Chryssa; Triantaphyllou, Sevi; et al.
ABSTRACT: We use stable isotope analysis of crop, faunal and human remains to investigate agricultural strategies and diet at EBA-LBA Archontiko and MBA-LBA Thessaloniki Toumba. Crop production strategies varied between settlements, phases and species; flexibility is also apparent within the crop stores of individual houses. Escalating manuring intensity at LBA Thessaloniki Toumba coincides with large co-residential 'blocks' geared towards hoarding of agricultural surpluses, spectacularly preserved by fire at nearby LBA Assiros Toumba. Faunal isotope values reflect a range of feeding strategies, including probable herding of cattle on C4 -rich coastal salt marshes, evident at Archontiko through to the LBA alongside bulk cockle harvesting. Palaeodietary analysis of LBA humans at Thessaloniki Toumba indicates that C3 crops represent the only plausible staples. Millet was a minor food but may have played a particular role in the sub-adult diet. Meat probably featured in supra-household food sharing and hospitality, associated with Mycenaean-style tableware in the LBA.